1994
DOI: 10.1557/proc-344-15
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Alumina Supported Catalysts Due to Spinel Formation

Abstract: An important cause of deactivation of alumina supported transition metal (oxide) catalysts is a solid state reaction between the active component and the support. We therefore studied the hightemperature behavior of Me layers (Me = Co, Ni, Cu and Fe) on polycrystalline α-A12O3 and γ- Al2O3 substrates. The samples were first oxidized at moderate temperatures and then annealed at high temperatures (up to 1000 °C) in O2, N2, or N2/O2 mixtures. The interfacial reaction to MeA12O4 was assessed using Rutherford Back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The results (see Figure 12) agree with those in Figure 11. Bolt et al (1994) reported that an important cause of deactivation of alumina supported transition metal (oxide) catalysts was a solid state reaction between the active component copper and the support alumina that forms CuAl 2 O 4 . This observation also could not be considered in this case as the presence of CuAl 2 O 4 spinel was observed in the fresh catalysts after calcining at 700ºC.…”
Section: Catalyst Activity Versus Time Studiesmentioning
confidence: 99%
“…The results (see Figure 12) agree with those in Figure 11. Bolt et al (1994) reported that an important cause of deactivation of alumina supported transition metal (oxide) catalysts was a solid state reaction between the active component copper and the support alumina that forms CuAl 2 O 4 . This observation also could not be considered in this case as the presence of CuAl 2 O 4 spinel was observed in the fresh catalysts after calcining at 700ºC.…”
Section: Catalyst Activity Versus Time Studiesmentioning
confidence: 99%
“…The ionizing radiations might also increase the number of active components by splitting them into small-sized particles besides modifying their acidic properties [12,13]. The doping with certain foreign oxides such as Li 2 O, K 2 O or ZnO hinders the metal oxide-support interactions thus increasing the stability of catalytically active constituents [16][17][18][19][20][21][22][23]. This treatment induced significant changes in the physicochemical characteristics of the treated solids such as the electrical, magnetic, textural and acidity features of the resulting solid catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The principal function of these materials called catalyst stabilizers is to prevent or to inhibit metal-support interaction. [10] Therefore, the knowledge of the phase diagram of metallic salts is very important, as it can provide the basis for elaborating igneous mixed oxides in a wide range.…”
Section: Introductionmentioning
confidence: 99%